2013
DOI: 10.1159/000350318
|View full text |Cite
|
Sign up to set email alerts
|

Use of Language Tests when Identifying Specific Language Impairment in Primary Health Care

Abstract: Objective: To evaluate the ability of language tests to identify children with specific language impairment (SLI) in primary health care. All the language tests presently in clinical use in Finland were applied. Method: All the children with SLI living in one city in Finland constituted the cohort. Test scores were collected from 83 subjects drawn from a birth cohort of 4,553 children. Finally 31 case-control pairs were studied. All SLI diagnoses were set in secondary health care. Test scores of 14 language te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…All participants were contacted through a larger study aiming to highlight the etiology, linguistic development and prognosis of SLI in the City of Vantaa, Finland 37,38 . The children in the SLI group had been diagnosed at the Helsinki University Central Hospital prior to school entry.…”
Section: Methodsmentioning
confidence: 99%
“…All participants were contacted through a larger study aiming to highlight the etiology, linguistic development and prognosis of SLI in the City of Vantaa, Finland 37,38 . The children in the SLI group had been diagnosed at the Helsinki University Central Hospital prior to school entry.…”
Section: Methodsmentioning
confidence: 99%
“…Published, norm-referenced assessments are considered essential diagnostic tools and should have standardised administrative, scoring and interpretative procedures with established validity, reliability and applicability for specified populations, in this case children with PSLI. 259,289 However, diagnosis is not the only purpose of assessment. Therapists need to draw on a range of information sources to support their clinical decision-making, including what to prioritise when a number of aspects require intervention (specifically in this research, which typology themes to target), how to track progress, how to determine when intervention is no longer required and how to measure outcomes.…”
mentioning
confidence: 99%
“…The main weakness of this study was the small number of the participants. Partially this was due to our relatively small cohort [30,31] and, thus, the number of case-control pairs remained small. This hampers possibilities to make clearcut conclusions about parameters which did not turn out to differ statistically significantly and allows only preliminary conclusions to be drawn from these parts of the data.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…The information of the pilot survey also conducted to the time scoring method used. Finally, the parents in this study filled in, during one week, daily questionnaires (see Appendix) where the observed time was between 5 pm and 9.30 pm each day and it was divided into [29][30][31]. The research included all children born in 1998 and 1999 who were diagnosed in specialist health care in Helsinki University Central Hospital as having SLI (ICD10 diagnosis F80.1 or F80.2) living in the city of Vantaa, Finland.…”
Section: Measurement Of Activities Atmentioning
confidence: 99%